Effect of Iron Loading on the Physicochemical Properties and Catalytic Activity of Fe/CeO2 Catalysts in Palm Kernel Shell Steam Gasification to Hydrogen - Mohamad, Mas Fatiha (2011)
—Hydrogen has emerged as one of the sustainable fuels in the next future that can be used in internal-combustion engine. Hydrogen produced from catalytic gasification of biomass generates clean and higher efficiencies automotive fuel. The use of catalyst in the biomass gasification is effective to elevate hydrogen content and to reduce tar formation. This work presents the development of Fe supported Ceria catalysts for palm kernel shell (PKS) steam gasification to hydrogen. 2.5-10wt% Fe/CeO2 catalysts have been prepared using incipient wetness impregnation method for 6 hours, dried at 120 oC for 16 hours and later calcined at 500 oC for 16 hours. The catalysts were characterized for their crystal structures using Powder X-Ray Diffraction (XRD), reducibility using Temperature Programmed Reduction (TPR), surface area, pore size and pore volume using N2 adsorption-desorption isotherm and morphology using Field Emission Scanning Electron Microscopy (FESEM). XRD results confirmed the formation of solid solution of iron-cerium oxide, with cubic CeO2 structure which is in agreement with FESEM images. As evaluated by surface area and pore analyzer, it was established that the Fe/CeO2 catalysts are nonporous and its surface area increases with increasing of Fe loading. TPR profiles show the overlapping of two reduction peaks, related to the surface Fe and CeO2. A shoulder peak evolved, attributed to the reduction of Fe3O4 to Fe. The 2.5wt % Fe/CeO2 catalyst indicates the maximum H2 production with the least formation of CO2 and CH4 from PKS steam gasification. It is likely that the formation of H2 reduces with increasing of Fe loading.